Effects of Positioning Aids on Understanding the Relationship Between a Mobile Map and the Environment - Kässi, Juho; Krause, Christina; Kovanen, Janne; Sarjakoski, Tiina (Human Technology, 2013)
Positioning technologies such as GPS enable mobile map applications to display a symbol representing an estimation of a user’s location on a mobile map, therefore acting as a positioning aid. Previous research on the cognitive processes involved in map reading suggests that map readers need at least two map–environment points (objects that are visualized on the map and perceived in the environment) for determining their location on a map. Hence, the positioning aid alone does not provide enough information for self-location. Using a field experiment, we assessed the effect of representing the user’s location on a map on the cognitive processes involved in self-location. The results show that positioning aids guide the search for map–environment points and narrow the area on the map that must be scanned for self-location.